Distribution and Evolution of Peroxisomes in Alveolates (Apicomplexa, Dinoflagellates, Ciliates). (29th November 2017) - Ludewig-Klingner, Ann-Kathrin; Michael, Victoria; Jarek, Michael; Brinkmann, Henner; Petersen, Jörn
Abstract: The peroxisome was the last organelle to be discovered and five decades later it is still the Cinderella of eukaryotic compartments. Peroxisomes have a crucial role in the detoxification of reactive oxygen species, the beta-oxidation of fatty acids, and the biosynthesis of etherphospholipids, and they are assumed to be present in virtually all aerobic eukaryotes. Apicomplexan parasites including the malaria and toxoplasmosis agents were described as the first group of mitochondriate protists devoid of peroxisomes. This study was initiated to reassess the distribution and evolution of peroxisomes in the superensemble Alveolata (apicomplexans, dinoflagellates, ciliates). We established transcriptome data from two chromerid algae ( Chromera velia, Vitrella brassicaformis ), and two dinoflagellates ( Prorocentrum minimum, Perkinsus olseni ) and identified the complete set of essential peroxins in all four reference species. Our comparative genome analysis provides unequivocal evidence for the presence of peroxisomes in Toxoplasma gondii and related genera. Our working hypothesis of a common peroxisomal origin of all alveolates is supported by phylogenetic analyses of essential markers such as the import receptor Pex5. Vitrella harbors the most comprehensive set of peroxisomal proteins including the catalase and the glyoxylate cycle and it is thus a promising model organism to investigate the functional role of this organelle in Apicomplexa.